Investigation into the influence of mild hypothermia on regulating ferroptosis through the P53-SLC7A11/GPX4 signaling pathway in sepsis-induced acute lung injury - Liujun Tao; Jie Xu; Liangyan Jiang; Juntao Hu; Zhanhong Tang (Intensive Care Medicine Experimental)
Abstract Background Sepsis-induced acute lung injury (S-ALI) significantly contributes to unfavorable clinical outcomes. Emerging evidence suggests a novel role for ferroptosis in the pathophysiology of ALI, though the precise mechanisms remain unclear. Mild hypothermia (32–34 °C) has been shown to inhibit inflammatory responses, reduce oxidative stress, and regulate metabolic processes. P53 has been reported to downregulate the transcriptional activity of solute carrier family 7 member 11 (SLC7A11), thereby limiting cystine uptake. This reduction in cystine availability compromises the activity of Glutathione peroxidase 4 (GPX4), a cystine-dependent enzyme, ultimately increasing cellular susceptibility to ferroptosis. However, it remains unclear whether mild hypothermia exerts protective effects through the P53-SLC7A11/GPX4 signaling pathway. This study investigates the influence of mild hypothermia on ferroptosis mediated by the P53-SLC7A11/GPX4 pathway in S-ALI. Methods This study utilized both in vivo and in vitro models. In the vivo model, 64 Sprague–Dawley rats were employed, with 40 analyzed for survival outcomes. Sepsis was induced using the cecum ligation and puncture (CLP) method, after which rats were subjected to either normothermic (36–38 °C) or mild hypothermic (32–34 °C) conditions for a duration of 10 h. Twelve hours post-surgery, blood samples, bronchoalveolar lavage fluid, and lung tissue samples were harvested for histological analysis, measurement of inflammatory markers, wet/dry ratios, blood gas analysis, assessment of oxidative stress and ferroptosis, Western blotting, and RT-qPCR analysis. In the in vitro model, RLE-6TN cells were exposed to lipopolysaccharide (LPS) for 24 h under normothermic and mild hypothermic conditions. These cells were then evaluated for cell viability, inflammatory markers, oxidative stress levels, ferroptosis markers, as well as Western blot and RT-qPCR analyses. Results CLP-induced sepsis led to elevated levels of inflammatory markers, increased lung injury scores, and heightened oxidative stress markers. These detrimental effects were significantly ameliorated by mild hypothermia. Furthermore, mild hypothermia reversed the modified expression of P53, SLC7A11, and GPX4 signaling molecules. Notably, mild hypothermia also improved the 5-day survival rate of CLP rats. Conclusion Mild hypothermia attenuates S-ALI and modulates ferroptosis through the P53-SLC7A11/GPX4 signaling pathway.